The construction and practice path of safety education mechanism in colleges and universities integrating the psychological characteristics of students in the new era - Li, Honglin (Frontiers in Psychology, 2023)
Background: With the rapid development of higher education in China, the scale of colleges and universities is expanding, and the phenomenon of campus socialization is becoming more and more obvious. In particular, the campus and its surrounding environment are becoming more and more complex, which brings many hidden dangers in university life. Objective: In order to improve the effectiveness of safety education in colleges and universities and maintain the long-term effectiveness of college students' safety awareness, the paper proposes the construction and practice path of college safety education mechanism that integrates the psychological characteristics of students in the new era. Methods: Security issues facing universities at home, this track identifies the relationship between campus security incidents and security education and advocacy. eight solutions to prevent and reduce incidents in schools. The paper proposes to give importance to the study of the security of college students, to create an awareness of security questions in the bank based on the recommendation algorithm, and to create to have online learning and testing for safety awareness. Results: The passing rate of 10 majors such as humanities, composition and theory of composition technology was 100%, accounting for 12% of the 83 enrolled majors, and the passing rate of 54 majors such as clinical medicine was over 90%. Conclusions: The safety online learning and testing system of college students' safety education is lively in form and highly accepted by students. The development of college students' safety education starts from the time of receiving the university admission notice, making full use of the "golden time", so as to effectively prevent and reduce the occurrence of campus safety accidents.